Strengthening slabs for punching shear using fibre reinforced polymer - Moreno, Carlos (2018)
Punching is generally associated to the application of concentrated loads or to the presence of columns. One of the main concerns related to flat slabs is its punching shear capacity at slab‐column connection, which is subjected to a very complex three‐dimensional stress state. Provided that bending capacity is installed, punching shear failure is characterized by the development of a truncated cone shaped surface at the slab‐column connection. Recurrently, there is the need to strengthen existing flat slabs against punching shear failure. The use of fibre‐reinforced polymer (FRP) is an innovative technology to strengthen concrete structures. In this paper, punching shear strengthening of flat slabs using carbon fibre reinforced polymer (CFRP) is studied. The experimental programme carried out by the authors includes four normal strength concrete slabs (1100×1100×100 mm3), with and without shear reinforcement, submitted to punching under a concentrated load. One of the specimens included typical bent‐down bars as shear reinforcement. Among available strengthening practices, the technique that consists on gluing CFRP on concrete surface have been tested within current experimental programme. Moreover, the near surface mounted (NSM) technique has also been tested within current experiments. Finally, a fourth specimen served as reference. The effects of shear reinforcement and of CFRP enhancing punching shear capacity are observed.